Pola asuh oleh ibu pada balita dengan berat badan di Bawah Garis Merah (BGM) di Surabaya - Novida D Airinda (Faculty of Social and Political Science, Universitas Airlangga, 2015)
Widely known as Asian rice producer in the past, Indonesia is still struggling with the issue of malnutrition until recent times. Growth and development of toddler are not maximal because their nutrition are not properly fulfilled since their early age. This research tries to explain mother's parenting pattern for toddler under the red line (bawah garis merah/BGM). The research was conducted in Kenjeran, District of Bulak, Surabaya, by interviewing and observing five informants. Data were analyzed by interview and observation, later to be interpreted. The research found that mother's knowledge about parenting and child's health are still influenced by belief that do not solve problem properly. Giving solid food to baby is a common thing and believed to resulted better than giving breast milk before their minimum age. This action is not medically recommended because baby has a minimum age to be able to digest solid food as complementer to breast milk.